PENGARUH MOTIVASI, LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN (Studi Kasus Di CV. Putra Leo) - Sundoro, 13.05.51.0115; Muhaimin, Muhaimin (Students Journal of Economic and Management, 2018)
This study aims to analyze the influence of motivation, work environment and compensation on employee performance on CV. Putra Leo Juwana. Thus, examines three independent variables, such as motivation, work environment and compensation that can affect the dependent variable of employee performance. Population in this research is employee CV. Putra Leo Juwana. Samples were taken as many as 100 respondents by using simple random sampling technique. Data were collected using survey method through questionnaires filled by consumers. The data were obtained analyzed by using Multiple Regression Analysis. This analysis includes: Validity, Reliability, and Multiple Regression Analysis. Hypothesis through T-test and F-test, and Determination Coefficient analysis (R2). Based on the Regression Analysis following equations are obtained Y = 0.281 X1 + 0.272 X2 + 0.391 X3. The compensation variable has the biggest influence on customer satisfaction is the location of 0.391, followed by the motivation variable of 0.281. While the working environment variables have the lowest influence than other variables of 0.272. The result of analysis using T-test can be seen that the three independent variables, such as motivation (X1), work environment (X2), and compensation (X3) partially significant influence on the dependent variable is employee performance (Y). Then, the results of analysis using the F-test can be seen that the three independent variables such as motivation (X1), work environment (X2) and compensation (X3) significantly influence the dependent variable together is employee performance (Y). The result of analysis using coefficient of determination known that 69,2% variation of employee performance can be explained by motivation, work environment and compensation. While the remaining 30.8% is explained by other variables not found in this study.Keywords : motivation, work environment, compensation, employee performance